Effect of organic and inorganic phosphate fertilizers and their combination on maize yield and phosphorus availability in a yellow earth in Myanmar - Aye, Tin Maung; Hedley, MJ; Loganathan, P; Lefroy, Rod D.B.; Bolan, NS (2009)
Phosphorus (P) deficiency is a major constraint for crop production in many parts of the world including Myanmar and field research into management of P fertilizers and P responsiveness of crops on infertile soils has been limited. The purpose of this study is to determine maize yield response to different forms of P fertilizers on an acidic (pH 4.9) P deficient (Olsen-P 8 mg kg-1) Yellow Earth (Acrisol) in Southern Shan State, Myanmar and to establish relationships between soil Olsen-P test values (0.5 M sodium bicarbonate extracted P) and maize yield. Field experiments were conducted during two cropping seasons. There were 15 treatments in total: P was applied at seven rates of a soluble P fertilizer as Triple superphosphate (TSP) (0–120 kg P ha-1) to establish a P response curve; one rate of a partially soluble P fertilizer (Chinese partially acidulated phosphate rock, CPAPR) and two organic P fertilizers (farmyard manure (FYM) and Tithonia diversifolia) at 20 kg P ha-1; combination of TSP and CPAPR at 20 kg P ha-1 with FYM and Tithonia at 20 kg P ha-1; an additional treatment (TSP 20 kg P ha-1 plus 2.5 t ha-1 dolomite) for assessing the liming effect of a local dolomite. In Year 1, applications of TSP at 40–60 kg P ha-1 produced near maximum grain yields, whereas in Year 2 this could be achieved with a reapplication of 20–30 kg P ha-1 on top of the residual value of the Year 1 application. In both years, CPAPR, TSP and Tithonia at 20 kg P ha-1 significantly increased maize grain yield, but FYM failed to increase grain yield. In Year 1, CPAPR and TSP effects on grain yield were higher than that of Tithonia but inYear 2 the effects were same for all these three treatments. In both years the combination of FYM (20 kg P ha-1) with TSP (20 kg P ha-1) produced significantly higher grain yield than TSP at 20 kg P ha-1whereas 40 kg P ha-1 ofTSP application did not significantly increase grain yield over the TSP application at 20 kg P ha-1. Similar results were obtained when half the P applied as CPAPR was substituted with P from Tithonia and FMP during the first year. The combined data from the two years experiment suggests that 90%ofmaximummaize grain yields can be obtained by raising the Olsen-P to 30–35 mg P ha-1 soil at the silking stage of growth. Olsen-P for the treatments at silking in Year 1 was: Control\FYM, Tithonia\TSP, CPAPR and in Year 2 was: Control\FYM\Tithonia\TSP, CPAPR. The results showed that for a long-term approach, repeated annual applications of Tithonia can be considered as a potential P source for improving soil P status in P deficient Yellow Earths.